Onset of Orthorhombic-tetragonal Structure in (YBa2Cu3O7-δ)1-x(Sn02)x Superconducting Ceramics - Shaari, Abdul Halim; Hashim, Mansor; Abd. Aziz, Sidek; Suradi, Jamil; Mohd Shafie, Naemah (Universiti Putra Malaysia Press, 1995)
High Tc superconductors, (YBa2Cu3O7-δ)1-x(Sn02)x with x ranging from 0.00 to 0.06 were prepared in air under optimum sintering conditions. Superconductivity and the onset of orthorhombic-tetragonal structure are discussed in relation to the results of X-ray diffraction studies. Meissner effect above liquid nitrogen temperature was observed for all the samples, suggesting the retention of orthorhombic structure in the system up to 6% Sn substitution.